2013
DOI: 10.1148/radiol.13122590
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Electroporation: Treatment Effect Is Susceptible to Local Environment and Tissue Properties

Abstract: ).q RSNA, 2013 Purpose:To study the effects of the surrounding electrical microenvironment and local tissue parameters on the electrical parameters and outcome of irreversible electroporation (IRE) ablation in porcine muscle, kidney, and liver tissue. Materials and Methods:Animal Care and Use Committee approval was obtained, and National Institutes of Health guidelines were followed. IRE ablation (n = 90) was applied in muscle (n = 44), kidney (n = 28), and liver (n = 18) tissue in 18 pigs. Two electrodes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…It has been clearly demonstrated that the effectiveness of LEDC is highly associated with the distribution of the electric field in the tissue (with the contributing variables including voltage, distance between the electrodes and depth of electrodes insertion) required to reach the optimal electrode configuration and tumor coverage [3,10,36,38,39,40,41]. Irreversible electroporation aims to completely extirpate the tumor or, at least, to dramatically modify the neoplastic microenvironment without damaging the surrounding tissues or vessels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that the effectiveness of LEDC is highly associated with the distribution of the electric field in the tissue (with the contributing variables including voltage, distance between the electrodes and depth of electrodes insertion) required to reach the optimal electrode configuration and tumor coverage [3,10,36,38,39,40,41]. Irreversible electroporation aims to completely extirpate the tumor or, at least, to dramatically modify the neoplastic microenvironment without damaging the surrounding tissues or vessels.…”
Section: Discussionmentioning
confidence: 99%
“…IRE may be reversible or irreversible, depending on the voltage applied and the peripheral decrease in field strength (edge area), whereby however only the irreversible region leads to visible tissue ablation [5]. One of the shortcomings of IRE today is the absence of dedicated, clinically validated protocols to be used in different tissue environments and for different tumour biologies [39,40]. In addition, no technical endpoint has yet been described that reliably predicts successful ablation of a tumour during the course of the intervention procedure [1,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on renal IRE were exclusively experimental or safety-oriented [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A complete histological analysis is still required to assess the completeness of tumour ablation and the nephron-sparing potential of IRE in RCC.…”
Section: Introductionmentioning
confidence: 99%
“…The clamp harboring the electrodes was also held at an angle with respect to the long axis of the nerve, in contrast to the perpendicular orientation in our study. These differences in local tissue environment and electrode orientation might increase the actual electric potential delivered to the nerves (14,15). We used ultrasound guidance during electrode insertion to avoid puncturing the nerve and to ensure that the neurovascular bundle was positioned perpendicularly at the midpoint of the paired electrodes.…”
Section: Discussionmentioning
confidence: 99%